Two cases of infantile-onset primary generalized glucocorticoid hypersensitivity and the effect of mifepristone - Xiu Zhao; Zhongwei Xu; Huiping Su; Rongfei Zheng; Min Zhan; Yuge Huang; Zhe Su (BMC, 2022)
Abstract Background Primary generalized glucocorticoid hypersensitivity (PGGH) is a very rare disease caused by terminal organ hypersensitivity to glucocorticoids for which the aetiology is unknown. The incidence of PGGH is extremely rare, especially in children. To date, the literatures about the etiology, prognosis and treatment of PGGH are scarce. Aim of the study is describing the cases of two Chinese children with infantile-onset PGGH in one family, one of whom died and one who was treated with mifepristone. They are the two youngest children with PGGH reported in the literature. Case presentation Two siblings with infantile-onset PGGH were affected in this family. The main manifestations of patient 1 were typical Cushing's syndrome-like manifestations, significantly aggravated symptoms after physiological doses of glucocorticoids and very low levels of serum cortisol and adrenocorticotropin hormone (ACTH) during attacks. After being diagnosed with PGGH, he was given guidance to avoid glucocorticoids and took mifepristone therapy for 5 months, and his symptoms improved. Patient 2 was the younger brother of patient 1, with similar manifestations to his brother at the age of 4 months. Patient 2 ultimately died at the age of 9 months. Conclusion PGGH is a very rare disease that can lead to death if not diagnosed and treated in a timely manner. This article describes the cases of the two youngest children with PGGH reported in the literature, one of whom improved after mifepristone treatment, and increases the knowledge of the clinical manifestations of and the treatment experience in PGGH.